Atomic oxygen in solid deuterium: Low-Temperature Physics and Chemistry in Cryomatrice - Danilychev, A. V.; Apkarian, V. A.; Kajihara, H.; Tanaka, S.; Koda, S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
Atomic oxygen is photogenerated in solid D2 by 193 nm irradiation of samples initially doped with molecular oxygen. The atoms are detected by laser induced fluorescence over the O ( 1S→ 1D) transition, which occurs at 559 nm, with a fluorescence lifetime of 230 ms. The absorption leading to this emission is indirect, attributed to O2(X) : O ( 3P) pairs. Complementary studies are carried in solid D2 co-doped with Xe and O2, in which in addition to ionic XeO centers, the atomic O ( 1S → 1D) transition with a radiative lifetime of 50 ms is observed. The photogeneration of the atomic centers, and stability of atomic and molecular emissions, are sensitive to sample preparation and thermal and irradiation histories. In annealed solids, at temperatures below 6.5 K, the atomic emission does not bleach, implying that the vertically prepared O (1D) atoms undergo intersystem crossing to form O (3P) rather than react with D2. The barrier to insertion on the O (1D)+D2 potential energy surface in solid D2 is explained as a many-body polarization effect. The recombination of O(3P) atoms can be initiated thermally, and monitored by their thermoluminescence over the molecular O2(A′ →X) transition. The thermal onset of recombination varies between 5.5 K and 9 K, depending on the sample preparation method. In all cases, the thermally induced recombination is catastrophic, accompanied by thermal runaway, pressure burst, and material loss. This is interpreted as indication that the process is initiated by self-diffusion of the host, consistent with the notion that atomic O centers stabilize the host lattice.